2022
DOI: 10.3390/cancers14133190
|View full text |Cite
|
Sign up to set email alerts
|

18FDG PET Assessment of Therapeutic Response in Patients with Advanced or Metastatic Melanoma Treated with First-Line Immune Checkpoint Inhibitors

Abstract: Background: Immune checkpoint inhibitors (ICI) are currently the first-line treatment for patients with metastatic melanoma. We investigated the value of positron emission tomography (PET) response criteria to assess the therapeutic response to first-line ICI in this clinical context and explore the potential contribution of total tumor metabolic volume (TMTV) analysis. Methods: We conducted a retrospective study in patients treated with first-line ICI for advanced or metastatic melanoma, with 18F-FDG PET/CT p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Respectively, when response to immunotherapy was defined by metabolic DCR, patients exhibiting disease control had a significantly longer survival than those with disease progression according to almost all metabolic criteria. These results come to substantiate previous works in the field reflecting the ability of metabolic response to ICIs, as assessed by [ 18 F]FDG PET/CT performed approximately 3–4 months after starting treatment, in stratifying longer-term patient outcome [ 23 , 34 ]. This time point for performing follow-up imaging appears sufficiently reliable, irrespective of the evaluation method used, and practical in terms of patient management.…”
Section: Discussionsupporting
confidence: 86%
“…Respectively, when response to immunotherapy was defined by metabolic DCR, patients exhibiting disease control had a significantly longer survival than those with disease progression according to almost all metabolic criteria. These results come to substantiate previous works in the field reflecting the ability of metabolic response to ICIs, as assessed by [ 18 F]FDG PET/CT performed approximately 3–4 months after starting treatment, in stratifying longer-term patient outcome [ 23 , 34 ]. This time point for performing follow-up imaging appears sufficiently reliable, irrespective of the evaluation method used, and practical in terms of patient management.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, as proposed by PET Response Evaluation Criteria for Immunotherapy (PERCIMT) and Immunotherapy-modified PET Response Criteria in Solid Tumors (imPERCIST) criteria, respectively, according to their number and size, new lesions may be considered a sign of progression if the metabolic activity is greater than a predetermined cut-off [ 260 ]. A relatively recent study by Rivas et al showed that the evaluation of ICI responses using metabolic imaging with imPERCIST5 and PERCIST5 (criteria used for conventional chemotherapy) was significantly associated with overall survival in 29 patients with advanced or metastatic cutaneous melanoma [ 261 ]. Among the many variants of SUV (e.g., mean SUV, maximum SUV), SUV corrected for lean body mass (SUL) was chosen for use with PERCIST because it is less susceptible to variations in patient body weight than the other SUV metrics [ 262 ].…”
Section: Molecular Imaging Techniquesmentioning
confidence: 99%
“…Risk stratification before treatment initiation is therefore of great interest for personalized treatment decisions. Noninvasive imaging techniques enable the quantitative assessment of the individual tumor burden on the molecular level (by 8F-labeled fluorodeoxyglucose positron-emission tomography (18F-FDG-PET)), as well as on the morphological and functional levels (by multiparametric MRI), including diffusion-weighted imaging (DWI) [ 6 ]. For CIT, previous studies indicated a possibly predictive value of the metabolic activity of the primary and secondary lymphoid organs in 18F-FDG-PET [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%